Peran Mahasiswa Dalam Pembinaan UMKM Melalui Kuliah Kerja Nyata Di Kelurahan Kolo - M.Rony Muhazir; Siska Andriani; Sholichatun Nisa; Fitrianingsih Fitrianingsih; Febi Febriyanti; Mazida Zahra; Irma Mardian (LPPM STIKES KESETIAKAWANAN SOSIAL INDONESIA, 2024)
The purpose of this program is to provide training and support to UMKM in order to be able to develop and improve the quality of products and marketing. In KKN activities, there are UMKM selected to obtain construction and support. Several stages in building UMKM through KKN include visits to UMKM, helping to market UMKM products through social media, and optimizing production management and marketing via social media. Through these activities, UMKM is expected to improve product quality, marketing, and business management. This journal provides an overview of how UMKM construction is carried out through Real Work College activities and provides insight into the efforts made to improve the quality and marketing of UMKM products.